Confronto-pilota fra N-acetilcisteina e un multicomposto contenente N-acetilcisteina terclatrata (c-NAC) sulla viscosità del muco in pazienti affetti da broncopneumopatia cronica - Cogo, R. (Progress in Nutrition, 2012)
Comparative pilot study between N-acetylcysteine (NAC) and a compound containing N-acetylcysteine terclatrate (c-NAC) on mucus viscosity in patients with chronic obstructive pulmonary disease